Pengembangan E-Modul Berbasis Inkuiri untuk Meningkatkan Kemampuan HOTS Siswa Sekolah Dasar di Kota Blitar - Anam, M. Saiful; Koeshandayanto , Supriyono; Mashfufah, Aynin; Maulana, Abdur Rofik (Universitas Nahdlatul Ulama Blitar, 2025)
This research aims to develop an inquiry-based e-module to improve the ability of HOTS on electrical materials to change the face of the world in grade VI elementary school. The development method used is the Lee and Owen method, which includes the stages of assessment / analysis (Needs assessment and Front-end analysis), Design, Development, Implementation, and Evaluation. Qualitative and quantitative approaches are used in analyzing data, using validation instruments, teacher response questionnaires, student response questionnaires, and HOTS ability tests as data collection tools. The results of data analysis showed that inquiry-based e-modules on electrical materials changing the face of the world had a feasibility rate of 86%, with the category